Population pharmacokinetics of intraperitoneal irinotecan and SN‐38 in patients with peritoneal metastases from colorectal origin - Pascale C. S. Rietveld; Sebastiaan D. T. Sassen; Niels A. D. Guchelaar; Ruben A. G. vanEerden; Nadine L. deBoer; Teun B. M. van denHeuvel; Jacobus W. A. Burger; Ron H. J. Mathijssen; Birgit C. P. Koch; Stijn L. W. Koolen (Wiley, 2024)
Abstract Peritoneal metastases (PM) are common in patients with colorectal cancer. Patients with PM have a poor prognosis, and for those who are not eligible for cytoreductive surgery (CRS) with or without hyperthermic intraperitoneal chemotherapy (HIPEC), palliative chemotherapy is currently the only option. Recently, we conducted a phase I trial (INTERACT) in which irinotecan was administered intraperitoneally (IP) to 18 patients ineligible for CRS‐HIPEC. The primary objective was to evaluate covariates influencing the PK profile of irinotecan and SN‐38 after IP administration. Secondly, a population PK model was developed to support the further development of IP irinotecan by improving dosing in patients with PM. Patients were treated with IP irinotecan every 2 weeks in combination with systemic FOLFOX‐bevacizumab. Irinotecan and SN‐38 were measured in plasma (588 samples) and SN‐38 was measured in peritoneal fluid (267 samples). Concentration‐Time data were log‐transformed and analyzed using NONMEM version 7.5 using FOCE+I estimation. An additive error model described the residual error, with inter‐individual variability in PK parameters modeled exponentially. The final structural model consisted of five compartments. Weight was identified as a covariate influencing the SN‐38 plasma volume of distribution and GGT was found to influence the SN‐38 plasma clearance. This population PK model adequately described the irinotecan and SN‐38 in plasma after IP administration, with weight and GGT as predictive factors. Irinotecan is converted intraperitoneal to SN‐38 by carboxylesterases and the plasma bioavailability of irinotecan is low. This model will be used for the further clinical development of IP irinotecan by providing dosing strategies.